2015
DOI: 10.12693/aphyspola.128.34
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Study of the Mechanical, Thermal and Optoelectronic Properties of the Cubic CsBaF3

Abstract: We have investigated the structural, elastic, electronic, optical and thermal properties of CsBaF3 perovskite using the full-potential linearized augmented plane wave method within the generalized gradient approximation and the local density approximation. Moreover, the modied BeckeJohnson potential (TB-mBJ) was also applied to improve the electronic band structure calculations. The ground state properties such as lattice parameter, bulk modulus and its pressure derivative were calculated and the results are c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 58 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…30 For cubic systems, there are three completely independent elastic constants i – e C 11 , C 12 , and C 44 . 31 Using these elastic constants, the other parameters e.g. G , ν , A , E , and B / G can be calculated using Voigt–Reuss–Hill eqn (1)–(6) .…”
Section: Elastic Characteristicsmentioning
confidence: 99%
“…30 For cubic systems, there are three completely independent elastic constants i – e C 11 , C 12 , and C 44 . 31 Using these elastic constants, the other parameters e.g. G , ν , A , E , and B / G can be calculated using Voigt–Reuss–Hill eqn (1)–(6) .…”
Section: Elastic Characteristicsmentioning
confidence: 99%
“…In PDOS, the La-5p states and O-2p state is coinciding with the fermi level it has been seen that the aluminium atoms don't affect much in the electronic band configuration. In general, due to the electronegativity of oxides the beginning of the wide band gap occurs [27][28][29]. Density of states is separated into three regions, lower valance band (LVB), upper valance band (UVB) and third region which is conduction band.…”
Section: Resultsmentioning
confidence: 99%
“…[6][7][8] The energy band gap of uoropyrocytes is oen large, so these compounds are technologically important. 9-11 KMgF 3 and BaLiF 3 are utilized in optical lithography steppers as vacuumultraviolet materials for lenses [11][12][13] and when doped with lanthanide ions Ce and Er, KMgF 3 also shows promise as a material for radiation dosimeters and scintillation. 14 Study of the compound SrCl 2 has found it to be an insulator with an indirect bandgap of 5.18 eV.…”
Section: Introductionmentioning
confidence: 99%